The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1103/physrevapplied.7.064009
|View full text |Cite
|
Sign up to set email alerts
|

From Half-Metal to Semiconductor: Electron-Correlation Effects in Zigzag SiC Nanoribbons From First Principles

Abstract: We performed electronic structure calculations based on the first-principles manybody theory approach in order to study quasiparticle band gaps, and optical absorption spectra of hydrogen-passivated zigzag SiC nanoribbons. Self-energy corrections are included using the GW approximation, and excitonic effects are included using the Bethe-Salpeter equation. We have systematically studied nanoribbons that have widths between 0.6 nm and 2.2 nm. Quasiparticle corrections widened the Kohn-Sham band gaps because of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…1(b) in the red open circles, the GW band gap of 2-ZSiCNR is 2.911 eV, which is more than three times larger than the LDA band gap (0.927 eV) and is also larger than a recent GW band gap (2.4 eV). 37 As shown in Fig. 2(b) in the red open circles, the GW band gap of 3-ZSiCNR is 0.804 eV, which is more than 9 times larger than the LDA band gap (0.093 eV) and is also almost more than two times larger than the recent GW band gap (0.45 eV).…”
Section: Qp Band Structurementioning
confidence: 79%
See 4 more Smart Citations
“…1(b) in the red open circles, the GW band gap of 2-ZSiCNR is 2.911 eV, which is more than three times larger than the LDA band gap (0.927 eV) and is also larger than a recent GW band gap (2.4 eV). 37 As shown in Fig. 2(b) in the red open circles, the GW band gap of 3-ZSiCNR is 0.804 eV, which is more than 9 times larger than the LDA band gap (0.093 eV) and is also almost more than two times larger than the recent GW band gap (0.45 eV).…”
Section: Qp Band Structurementioning
confidence: 79%
“…It is excitingly found that the GW band gap of 3-ZSiCNR is 0.804 eV, which is almost more than two times larger than the Alaal et al 37 GW band gap (0.45 eV). The GW band gap of 2-ZSiCNR is 2.911 eV, which is also larger than the Alaal et al 37 GW band gap (2.4 eV).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations